Slappy New Year! - Stine, R. L. (New York : Scholastic, 2010)
Ray Gordon, having promised his parents he will not scare his younger brother again in order to have a New Year's Eve party, begins to notice that whenever mean-spirited things happen to his sibling the wooden dummy, Slappy, he got from Jonathan Chiller's HorrorLand gift shop is around and worries he may have accidently brought the doll to life.
4.7
5-8
Keywords: Amusement parks -- Juvenile fiction; Brothers -- Juvenile fiction; Phobias -- Juvenile fiction; Puppets -- Juvenile fiction; Amusement parks -- Fiction; Brothers -- Fiction; Phobias -- Fiction; Puppets -- Fiction; Amusement parks -- Fiction; Brothers -- Fiction; Phobias -- Fiction; Puppets -- Fiction